Pengaruh Model Pembelajaran Teaching Factory (TEFA) Berbantuan Aplikasi Desmos terhadap Kemampuan Pemecahan Masalah Matematis Siswa Berbasis Kearifan Budaya Batak Toba - Talitha Eriliyah Wardhana Br Tobing; Yenni Novita Harahap; Khoiruddin Matondang (Yayasan Literasi Sains Indonesia, 2026)
This study aims to analyze the effect of the Teaching Factory (TEFA) learning model assisted by the Desmos application based on Batak Toba local wisdom on students’ mathematical problem-solving abilities. The research employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The subjects were eleventh-grade science students of SMA Muhammadiyah 7 Serbelawan, consisting of an experimental class and a control class with 38 students each. The experimental class was taught using the TEFA model assisted by Desmos integrated with Batak Toba cultural contexts, while the control class applied a scientific learning model based on local culture. The research instrument was a mathematical problem-solving ability test that had been validated and tested for reliability. Data analysis included normality testing, homogeneity testing, independent sample t-test, and N-Gain analysis. The results indicated that students taught using the TEFA model assisted by Desmos achieved higher problem-solving abilities than those in the control class, with mean posttest scores of 90.34 and 85.94, respectively. The t-test results showed a t-value of 3.925, exceeding the t-table value of 1.993, with a significance level of 0.000 < 0.05. Furthermore, the N-Gain value of the experimental class was 0.81, categorized as high. These findings indicate that the Teaching Factory learning model assisted by the Desmos application based on Batak Toba cultural wisdom has a significant and positive effect on improving students’ mathematical problem-solving abilities.